High performance work practices and well-being at restaurant work - Cajander, Niko; Reiman, Arto (European journal of tourism, hospitality and recreation, 2019)
This study focuses on human resource management (HRM) and high performance work practices in small restaurants. Empirical material is collected through interviews aimed at individuals working in the restaurant industry. In the first phase of this study in 2010, ten employees were interviewed, and in the second phase in 2018, five of them were re-interviewed. In 2010, the interviewees were working as employees in a restaurant where well-being was constantly challenged during work. During the second round of interviews in 2018, the interviewees had continued their careers in the sector and worked in five different restaurants. The findings indicate the signs of rapid change within the specific restaurant studied and provide insights into managing well-being at work in the restaurant industry as a whole – an industry that is constantly facing new types of challenges related to new working modes. Findings indicate that well-being at work is a holistic combination of individual and work-level activities; thus, a comprehensive approach to HRM is required.